Deferring Routine Wrist Radiography Does Not Affect Management of de Quervain Tendinopathy Patients - Kazmers, Nikolas H.; Liu, Tiffany C.; Wu, Chia H.; Steinberg, David R.; Bozentka, David J.; Levin, L. Scott; Gray, Benjamin L. (Journal of Wrist Surgery, 2018)
Background Obtaining wrist radiographs prior to surgeon evaluation may be wasteful for patients ultimately diagnosed with de Quervain tendinopathy (DQT).Questions/Purpose Our primary question was whether radiographs directly influence treatment of patients presenting with DQT. A secondary question was whether radiographs influence the frequency of injection and surgical release between cohorts with and without radiographs evaluated within the same practice.Patients and Methods Patients diagnosed with DQT by fellowship-trained hand surgeons at an urban academic medical center were identified retrospectively. Basic demographics and radiographic findings were tabulated. Clinical records were studied to determine whether radiographic findings corroborated history or physical examination findings, and whether management was directly influenced by radiographic findings. Frequencies of treatment with injection and surgery were separately tabulated and compared between cohorts with and without radiographs.Results We included 181 patients (189 wrists), with no differences in demographics between the 58% (110 wrists) with and 42% (79 wrists) without radiographs. Fifty (45%) of imaged wrists demonstrated one or more abnormalities; however, even for the 13 (12%) with corroborating history and physical examination findings, wrist radiography did not directly influence a change in management for any patient in this series. No difference was observed in rates of injection or surgical release either upon initial presentation, or at most recent documented follow-up, between those with and without radiographs. No differences in frequency, types, or total number of additional simultaneous surgical procedures were observed for those treated surgically.Conclusion Wrist radiography does not influence management of patients presenting DQT.Level of Evidence This is a level III, diagnostic study.
Keywords: de Quervain tendinopathy; de Quervain treatment; wrist radiographs; radiography